Acute toxicity of arumanis mango leaves (Mangifera indica L.) extract against zebrafish (Danio rerio) embryos - Darniwa, Adisty Virakawugi; Cahyanto, Tri; Rahayu, Ira; Ulfa, Risda Arba; Adawiyah, Ayuni (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Arumanis is one of the cultivars of Indonesian mangoes used as a horticultural commodity. Young leaves arumanis can be used for traditional herbal medicine. Pharmacological activity of young leaf arumanis extract are known to be antidiabetic, anticancer, antibacterial, anti-inflammatory, and analgesic effects. However, it is necessary to carry out toxicity testing before young leaf arumanis extract is used in traditional herbal medicine. This study aimed to determine the LC50 value of young leaf arumanis extract and identify the hatching time of embryos, heart rate of larvae, swimming movement of larvae, and malformations in both embryos and larvae. Forty five embryos of zebrafish were exposed to several concentrations of young leaf arumanis extract at 24 h post-fertilization until 96 h post-fertilization. Percentage of embryonic death calculated using probit analysis model LC50. Hatching rate, swimming movements, and heart rate were analyzed using the IBM SPSS software version 26. The LC50 values of the young leaf arumanis extract were 42.65μg/mL at 96 hpf and also 42.65μg/mL at 72 hpf. The embryotoxic effects at high concentrations of the extract are hatching delay and decreasing heart rate. The extract also caused abnormalities in embryo morphology, including pericardial edema and tail bending.